Studying the possibility of harvesting floods in Wadi Tavalgo Basin in Mizdah region, Libya using GIS & RS. (Libya Journal of Geographical Studies, 2026)
The study addressed the possibility of harvesting floodwaters in the valley of Tefalgu basin using remote sensing and geographic information systems, as well as understanding the flood risks in the valley basin and the potential to avoid them. The basin covers an area of 2,059 km². The study area encompasses geological formations dating back to the Upper Cretaceous, covering 93.5% of the region, making them the most exposed geological formations in the basin. The elevation of the basin's surface ranges from 234 meters at its outlet in Wadi Souf El-Jin to 952 meters above sea level at the top of Jebel Nafusa between Gharyan and Al-Asabi'a, a significant difference of 718 meters, with elevations gradually varying in between. The slope of the basin ranges from 0 to 40 degrees, and regarding the slope direction, the predominant direction is south at 14%, followed by southeast at 13.9%, east at 13.8%, and southwest at 13%, and these directions play a key role in determining the surface runoff direction of rainwater. The dominant soil in the Wadi basin is mixed soil with medium to coarse materials, accounting for 99.7%, while the remaining 0.3% is sandy clay soil. The study revealed six types of land cover, with shrubs occupying most of the area at 96.1%. The study concluded the feasibility of applying water harvesting and proposed several sites for constructing dams to capture rainwater and mitigate the risk of floods.
Keywords: valley of Tefalgu; water harvesting; GIS; RS